'A whole lot of uncertainty': A qualitative study exploring clinical medical students' experiences of uncertainty stimuli. Issue 7 (16th February 2022) - Stephens, Georgina C.; Sarkar, Mahbub; Lazarus, Michelle D.
Abstract: Introduction: Uncertainty tolerance (UT) describes how individuals respond to stimuli of uncertainty, with low UT among medical doctors and students linked to negative outcomes such as burnout. UT research in medical education has focused on measuring the construct, with little research seeking to understand how medical students experience uncertainty. Hence, knowledge on how education may shape students' UT development is lacking. As a first step to understanding students' UT, we asked 'How do medical students, in their clinical years, experience uncertainty stimuli?' Methods: Utilising a social constructionist approach, we undertook a qualitative study with 41 clinical years medical students. Data were collected during the 2020 academic year employing in‐semester reflective diary entries (n = 230 entries), and semi‐structured interviews at the end of semesters (n = 40 interviews). Data were analysed by framework analysis. Results: Students described three major themes of uncertainty stimuli: (i) educational uncertainty, (ii) professional uncertainty and (iii) clinical uncertainty. Educational uncertainty was the dominant stimulus described by students and represents unknowns related to what students needed to learn and how to learn within the context of clinical placements. Professional uncertainty encompassed questions about who students are as developing professionals and who they would be as doctors. Clinical uncertainty was the least represented stimulus and concerned aspects of patient care where the body of medical knowledge is unable to provide clear answers. Conclusions: Our findings indicate that clinical learners experience wide reaching uncertainties and suggest that students' stimuli may differ from those of clinicians with more established knowledge and careers. This work now paves the way forward in developing educational interventions to foster UT, such as modifying uncertainties not integral to learning, and purposefully introducing clinical uncertainties relevant to students' learning stage. Abstract : Stephens et al. demonstrate that clinical medical students experience uncertainty in a wide variety of ways that often differ from the experiences of clinicians with more established knowledge and careers.